2002
DOI: 10.1016/s1044-0305(01)00344-0
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase reactions of charged phenyl radicals with neutral biomolecules evaporated by laser-induced acoustic desorption

Abstract: A generally applicable method for the study of phenyl radicals' reactions with neutral biomolecules in the gas phase is demonstrated. Neutral biomolecules were evaporated into a Fourier-transform ion cyclotron resonance mass spectrometer (FT-ICR) by means of laserinduced acoustic desorption (LIAD) and subsequently reacted with trapped charged phenyl radicals. The structural integrity of the evaporated alanylalanine molecules was verified by reaction with dichlorophosphenium ions. Examination of the reactions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…11 Ionization of the desorbed molecules by well characterized chemical reactions has been demonstrated to be an effective approach for the analysis of non-volatile, thermally labile compounds. 5,6 One of the limitations of LIAD experiments, as utilized in our laboratories, is the inability to analyze species with large molecular weights. Depending on the type of analyte being studied, different high mass limits exist.…”
Section: Introductionmentioning
confidence: 99%
“…11 Ionization of the desorbed molecules by well characterized chemical reactions has been demonstrated to be an effective approach for the analysis of non-volatile, thermally labile compounds. 5,6 One of the limitations of LIAD experiments, as utilized in our laboratories, is the inability to analyze species with large molecular weights. Depending on the type of analyte being studied, different high mass limits exist.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry offers a convenient means for the isolation and the study of transient intermediates, if these are charged. Kenttämaa and coworkers [11][12][13][14][15][16] and, more recently, our group [17][18][19][20][21] have demonstrated that organic radicals containing inert charges, including alkali metal ion or quaternary pyridinium sites, primarily react at their radical centers. Such systems can therefore serve as templates for the investigation of the gas-phase chemistry of the corresponding neutral radicals.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of soft ionization sources such as MALDI [2] and ESI [3], it has become possible to determine the intrinsic gas-phase properties of amino acids and other compounds of biological relevance in modern mass spectrometers [4 -11]. While it is now relatively straightforward to form protonated/deprotonated amino acids with these soft ionization sources, generating sufficient quantities of neutral amino acids for gas-phase equilibrium studies is still a challenge [6,12,13]. On the other hand, forming proton-bound dimer ions containing an amino acid and a reference compound for kinetic method experiments has become routine [5, 11, 14 -22].…”
mentioning
confidence: 99%